Back Cover: 3 D Co3(PO4)2–Reduced Graphene Oxide Flowers for Photocatalytic Water Splitting: A Type II Staggered Heterojunction System (ChemSusChem 22/2016). Issue 22 (17th November 2016) - Samal, Alaka; Swain, Smrutirekha; Satpati, Biswarup; Das, Dipti Prakasini; Mishra, Barada Kanta
Abstract : The Back Cover picture shows the unique visible‐light‐driven activity of 3 D Co3 (PO4 )2 –reduced graphene oxide flowers towards hydrogen generation through water splitting. More details can be found in the Full Paper by Samal et al. onpage 3150 in Issue 22, 2016 (DOI:10.1002/cssc.201601214 ).